Bilberry-containing supplements on severe dry eye disease in young and middle-aged adults: A 3-month pilot analysis - Yu, Wing Y.; Chan, Lily Y. L.; Chung, Aden; Lee, Paul H.; Woo, George C. (Frontiers in Nutrition, 2023)
Purpose: To explore the effect of bilberry and fish oil combination supplement on a small clinical sample patient-base with severe dry eyes. Methods: Twenty-four subjects were recruited with twelve randomly assigned to the intervention and control groups, respectively. Inclusion criteria included severe dry eye symptoms determined by scores >33 from the Ocular Surface Disease Index (OSDI) questionnaire. The intervention group was instructed to take an oral supplement with key ingredients of 600 mg bilberry extract and 240 mg DHA-refined fish oil once daily for three months. The control group did not take any supplement. Mean changes in OSDI score, non-invasive tear break-up time (NITBUT), phenol red thread test (PRT), and percentage of meibomian gland openings were used as outcome measures. Testing was done at baseline, 1-month and 3-months follow-up. Comparison between the treatment and control groups, and the younger adult and middle-age groups were performed. Results: The mean baseline values for the treatment and control groups were not clinically different. The OSDI score, NITBUT, PRT and percentage of meibomian gland openings improved after taking the supplements for 3 months. The OSDI score, NITBUT, and PRT tests showed clinical improvements between the intervention and control groups. These improvements were consistent between the two age groups. Conclusion: This study suggested preliminary improvements in signs and symptoms of severe dry eyes that was independent of age after taking dietary supplementation of bilberry extract and fish oil for 3 months. Further studies using more device-based measures and a placebo supplement are warranted.